SIFD as a novel cause of severe fetal hydrops and neonatal anaemia with iron loading and marked extramedullary haemopoiesis. Issue 3 (21st October 2017) - Barton, Chris; Kausar, Sabiha; Kerr, Deborah; Bitetti, Stefania; Wynn, Rob
Abstract : SIFD describes a heritable, syndromic condition characterised principally by sideroblastic anaemia (SA) with immunodeficiency, fevers and developmental delay, arising in mutations within the TRNT1 gene. Other clinical manifestations of SIFD include cardiomyopathy, seizures, sensorineural hearing loss, renal dysfunction, metabolic abnormalities, hepatosplenomegaly and retinitis pigmentosa. Presentation of SIFD is variable but typically in early childhood with SA or with fever. In this report, we extend the described SIFD phenotype. We describe a kindred in which the index case presented with fetal hydrops, and early neonatal death, and the second child had severe anaemia at delivery. Both cases had prominent extramedullary erythropoiesis and numerous circulating nucleated red blood cells.